Evidence and gaps in the literature on HIV/STI prevention interventions targeting migrants in receiving countries: a scoping review - Faustine Kyungu Nkulu-Kalengayi; Robert Jonzon; Charlotte Deogan; Anna-Karin Hurtig (Taylor & Francis Group, 2021)
Background Evidence suggests that migration increases vulnerability to human immunodeficiency virus (HIV) and other sexually transmitted infections (STI). However, there is limited knowledge about what has been done or needs to be done to address migrants' vulnerability in receiving countries. Objectives A scoping review was carried out to map the existing literature in this field, describe its characteristics, identify gaps in knowledge and determine whether a Sexual and Reproductive Health and Rights (SRHR)-perspective was applied. Methods We used the Arksey and O'Malley framework and the Joanna Briggs Institute guidelines for scoping reviews and subsequent enhancements proposed by other authors. We searched three databases and grey literature to identify relevant publications. Results A total of 1,147 records were found across the three electronic databases and compiled. Of these, only 29 papers that met the inclusion criteria were included. The review shows that research in this field is dominated by studies from the USA that mostly include behavioural interventions for HIV and HBV prevention among migrants from Latin America and Asian countries, respectively. None of the interventions integrated an SRHR perspective. The intervention effects varied across studies and measured outcomes. The observed effects on knowledge, attitudes, perceptions, behavioural intentions and skills were largely positive, but reported effects on testing and sexual risk behaviours were inconsistent. Conclusions There is a need for good quality research, particularly in parts of the world other than the USA that will address all STIs and specifically target the most vulnerable subgroups of migrants. Further research requires greater scope and depth, including the need to apply an SRHR perspective and incorporate biomedical and structural interventions to address the interacting causes of migrants' vulnerability to HIV/STIs.